2017
DOI: 10.1590/1983-40632016v4743525
|View full text |Cite
|
Sign up to set email alerts
|

Agro-morphological characterization and genetic divergence assessment in bush snap bean genotypes1

Abstract: The characterization and identification of genetically divergent parents for crosses are important tasks in snap bean breeding programs, for a greater availability of cultivars to growers. This study aimed at characterizing bush snap bean genotypes originating from different countries; assessing the genetic divergence between the genotypes and the genetic variability extent, concerning 12 agro-morphological traits; and determining the relative importance of these traits for the genetic divergence. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…The ratio between genotypic coefficient of variation and environmental coefficient of variation (GCV/ECV) was larger than the unit for all traits, with high estimates, therefore, it is additional evidence that the traits are promising for successful selection (Correa et al, 2015 andVaz et al, 2017). The high genetic variations are probably due to the nature of the investigated genetic materials, since they are genebank germplasm, consist of landraces and advanced cultivars which widely differ in their traits.…”
Section: Genetic Variabilitymentioning
confidence: 93%
See 2 more Smart Citations
“…The ratio between genotypic coefficient of variation and environmental coefficient of variation (GCV/ECV) was larger than the unit for all traits, with high estimates, therefore, it is additional evidence that the traits are promising for successful selection (Correa et al, 2015 andVaz et al, 2017). The high genetic variations are probably due to the nature of the investigated genetic materials, since they are genebank germplasm, consist of landraces and advanced cultivars which widely differ in their traits.…”
Section: Genetic Variabilitymentioning
confidence: 93%
“…The inter-cluster distances and the mean performance of the accessions should be considered together as the genetically divergent parents may not have the best combining ability unless they also have good performance of the traits being improved (Vaz et al, 2017) . Consequently, the crossing between the best performing genotypes from diverse clusters is recommended.…”
Section: Tocher's Optimization Methods Of Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating only the conventional system, in the Cerrado region, Vaz et al (2017) found yield ranging from 1,536 to 3,398 kg ha -1 . The high incidence and controlling difficulty of Diabrotica speciosa in the initial phase, and of Bemisia tabaci, from the flowering stage onwards, may have been the main responsibles for the low yield, specially in the conventional system, despite the adopted controlling measures using recommended pesticides.…”
Section: /6mentioning
confidence: 99%
“…These have contributed to the expansion of snap beans crop in several regions of Brazil, with it standing out as a good low operational cost option for Fall/ Winter in irrigated areas, since they enable the mechanization of most cultivation operations. Moreover, these cultivars produce good quality pods, which in turn has led to the greater demand for this group by producers (Francelino et al, 2011;Andrade et al, 2017;Peixoto & Cardoso, 2016;Vaz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%